The variation in the Rainfall average countor lines and their effect in the dust storm frequency in Iraq - Jassim, Nahla; Habbeb, Eman; Hantosh, Tahir (Iraqi Journal of Science, 2024)
The results reflect the remarkable variation on annual rainfall between the seventies and twenty one century for all the studied meteorological stations. Therefore, there were an increase of the suspended dust over all the studied meteorological stations.